Analisis Kebudayaan dalam Karya Sastra Willem Iskandar “Si Bulus-Bulus Si Rumbuk-Rumbuk” - Kartika Siregar; Djono Djono; Leo Agung (Department of History, Faculty of Humanities, Diponegoro University, 2018)
This article aims to discuss the literary work of Si Bulus-Bulus Si Rumbuk-Rumbuk written by Willem Iskandar in cultural approach. Willem Iskandar was a writer who produced literary works to build a revolutionary spirit for the advancement of South Tapanuli. The literary work he produced implied a passion for change. The literary works that he wrote were very much about the culture in South Tapanuli. Si Bulus-Bulus Si Rumbuk-Rumbuk is his most popular work. Many messages are written in his work. The depiction of culture as outlined in his work invites the people of South Tapanuli to be more eager to make local wisdom a cultural heritage that must be preserved. In addition, his work also describes the geographical conditions and conditions in South Tapanuli. This work was a great asset for advancing education in South Tapanuli at that time. This article was prepared using qualitative descriptive methods based on literature studies and field research. A review of Si Bulus-Bulus Si Rumbuk-Rumbuk works conducted by understanding the text and then interpreting it to obtain the values contained in it.